Răspunsuri

2014-11-19T14:04:51+02:00
54-16:{ [ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2 } =52
16:{ [ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2 } =54-52
16:{ [ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2 }=2
[ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2=16:2
[ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2=8
[ 36 - 6 ×4 :(X - 4 ×5 )] : 5=8-2
[ 36 - 6 ×4 :(X - 4 ×5 )] : 5=6
[ 36 - 6 ×4 :(X - 4 ×5 )] =6x5
36 - 6 ×4 :(X - 4 ×5 )=30
6 ×4 :(X - 4 ×5 )=36-30
6 ×4 :(X - 4 ×5 )=6
24 :(X - 20 )=6
X - 20=24:6
X - 20=4

x=4+24
x=24
Cel mai inteligent răspuns!
2014-11-19T14:06:34+02:00
54-16:{ [ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2 } =52
16:{ [ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2 } =54-52
16:{ [ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2 }=2
[ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2=16:2
[ 36 - 6 ×4 :(X - 4 ×5 )] : 5+2=8
[ 36 - 6 ×4 :(X - 4 ×5 )] : 5=8-2
[ 36 - 6 ×4 :(X - 4 ×5 )] : 5=6
[ 36 - 6 ×4 :(X - 4 ×5 )] =6x5
36 - 6 ×4 :(X - 4 ×5 )=30
6 ×4 :(X - 4 ×5 )=36-30
6 ×4 :(X - 4 ×5 )=6
24 :(X - 20 )=6
X - 20=24:6
X - 20=4
X=4+20
X=24